ANALYSIS OF ANTHESEDENT AND TAXPAYER AWARENESS CONSEQUENTS OF COMPLIANCE LEVELS IN FULFILL ITS TAXATION OBLIGATIONS - M. Gunawan Setyadi; N. Dicky Sumarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study is to provide conceptual information regarding the role of exogenous variables, namely understanding the implementation of self-assessment systems, service quality, perceptions of taxation sanctions on the mediation variable of taxpayer awareness and taxpayer compliance endegenus variables (WP). Specifically, it provides information on the effect of understanding the implementation of self-assessment systems, service quality, and perception of taxpayers on taxation sanctions on taxpayer compliance which is moderated by the awareness of taxpayers. This study takes the population of individual and corporate taxpayers who carry out their obligations at KPP Pratama Surakarta. The sampling method was carried out using purposive sampling and the number of samples was determined as many as 150 respondents. The analysis method used is Structure Equation Modeling (SEM) analysis with AMOS software (Santoso, 2018). This research is expected to provide empirical information about the effect of understanding the implementation of self-assessment systems, service quality, taxpayer perceptions of tax penalties on taxpayer awareness. The influence of WP awareness on WP compliance. The awareness function of taxpayers mediates the influence of the understanding of the implementation of the self assessment system, service quality, the perception of taxpayers on taxation sanctions and affects taxpayers' compliance. The conclusion of the study is to empirically prove that taxpayer compliance is largely determined by the level of taxpayer awareness, the higher the taxpayer's awareness will have an impact on the higher taxpayer compliance and vice versa. Meanwhile, taxpayer awareness is strongly influenced by the perception of taxpayers about tax sanctions, not influenced by the understanding of the implementation of the self-assessment system or the quality of service so that it proves This research also proves that taxpayer awareness is proven to fully mediate the influence between perceptions of tax sanctions on taxpayer compliance and does not mediate the influence between the understanding of the implementation of the self assessment system, service quality on mandatory compliance. Keywords: self assessment system, service quality, tax sanctions, taxpayer awareness, taxpayer compliance